Interior “Umyah Blambangan” (Pusat Kebudayaan dan Pariwisata Banyuwangi) - Pricillia Yolanda Wijaya; Laksmi Kusuma Wardani; Stephanie Melinda Frans (Intra, 2018)
Banyuwangi is a regency that rich in culture and natural resources as a tourist destination. Its strategic location and rapidly growing infrastructure facilities make this regency has great potential to become a big tourist area. Umyah Blambangan aims is to be a conservation, education, and recreation site. The design concept has four main points as representation of four main pillars of traditional house of Osing Tribe, that is Culture, Tourism, Experience, and Blambangan. This facility is designed to help tourists, so they can get to know Banyuwangi in one place that has a traditional atmosphere but also has a modern and technological side. With this design, information about Banyuwangi will be displayed in areas with historical, cultural, and tourism themes with attractive interactive designs, complemented by culinary center, souvenir centers, and tourism ticketing area.